What A Shocking of Islam Perspective: Between Reality and Expectations - Chaerul Anam M. Bintang; Nurlathifah Thulfitrah B. (Journal of Contemporary Gender and Child Studies, 2026)
This study aimed to discuss about phenomenology in Islam. The philosophy of Islam was created by the friction between Islam and philosophy itself, which is based on the previous Muslim scholar. It was mean, that nowadays, Islam is still shackled or it can say that “has not move on” from the romantic histories in the past, or in another hand, it can say that Islam still used the oldest perspective because of the longest history which point about the world civilization and gave the influential figure of it. As we are known, Islam has powerless to break modernism. Some literature offers the solutions which mean that could be the direction for the current solution nowadays, and it will include the reconstruction of the curriculum which is still “highest” and that’s mean it needs to be “grounded” or lower. So, it could be directly connected with the empirical problem. Moreover, education needs to involve and maximize the educator's competencies; pedagogic, professional, personal, and social.